Epistemology and Resistance to the Meaning of Religious Moderation in Islamic Boarding Schools - Muhtador, Moh.; Shofaussamawati, Shofaussamawati; Rahman, Zaizul Ab (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The concept of religious moderation has been widely promoted by the Ministry of Religious Affairs, but it has not fully reached pesantren, potentially leading to conflicts. This article aims to uncover the various meanings of moderation among the Santri and to examine the epistemological framework derived from the kitab kuning (classical Islamic texts). The exegesis-phenomenology method was used by asking the Santri for their views on religious moderation and confirming their behaviors to understand the sources and methods of their knowledge. The findings show that the meaning of religious moderation in pesantren is natural-adaptive, and its epistemology is characterized as Bayani-cognitive. This article contributes theoretically to understanding the various meanings of moderation in pesantren and practically to policy-making for the widespread dissemination of religious moderation in religious institutions.Gagasan moderasi beragama telah disebarkan secara luas oleh Kementerian Agama, namun belum sepenuhnya mencapai pesantren, ini berpotensi menimbulkan konflik. Artikel ini bertujuan mengungkap varian makna moderasi di kalangan santri dan meneliti bangunan epistemologi yang bersumber dari kitab kuning. Metode exegesis-fenomenologi digunakan dengan meminta pandangan santri tentang moderasi beragama dan mengkonfirmasi perilaku mereka untuk mengetahui sumber dan metode pengetahuan mereka. Temuan menunjukkan bahwa makna moderasi beragama di pesantren bersifat natural-adaptif dan epistemologinya bercorak bayani-kognitif. Artikel ini berkontribusi secara teoritis dalam memahami varian makna moderasi di pesantren dan secara praktis bagi kebijakan penyebaran moderasi beragama di lembaga keagamaan.